HUBUNGAN MOTIVASI KERJA DAN KOMPETENSI PEDAGOGIK GURU DENGAN PRESTASI BELAJAR SISWA - Jumriah, Jumriah; Faisal, Muhammad; Syawaluddin, Ahmad (Universitas Negeri Makassar, 2025)
This study is an ex post-facto research that aims to find out whether there is a relationship between Work Motivation and Teacher's Pedagogic Competence and Student Learning Achievement. The independent variables in this study are work motivation and pedagogic competence of teachers, while the bound variable is Student Learning Achievement. The population in this study is all teachers at Tombiano State Elementary School, West Tojo District, Tojo Una-Una Regency which amounted to 15 people, both teachers who have civil servant status and teachers who are still honorary, while the sample is teachers at Tombiano State Elementary School who have civil servant and non-civil servant status. The data of the research results was obtained by distributing written questionnaires in the form of questionnaires. Data analysis techniques in quantitative research use statistics, namely descriptive statistics and inferential statistics. The results of the study show that the picture of pedagogic competence is in the high category, the teacher's work motivation is in the very high category and the student learning achievement is in the high category. There is a positive and significant relationship between pedagogic competence and work motivation together (simultaneously) on the Learning Achievement of Tombiano State Elementary School Students, West Tojo District, Tojo Una-Una Regency